Sustained acoustic medicine for the treatment of musculoskeletal injuries: a systematic review and meta-analysis - Sandra L. Winkler; Anthony E. Urbisci; Thomas M. Best (BMC, 2021)
Abstract Background Musculoskeletal injuries account for 10 million work-limited days per year and often lead to both acute and/or chronic pain, and increased chances of re-injury or permanent disability. Conservative treatment options include various modalities, nonsteroidal anti-inflammatory drugs, and physical rehabilitation programs. Sustained Acoustic Medicine is an emerging prescription home-use mechanotransductive device to stimulate cellular proliferation, increase microstreaming and cavitation in situ, and to increase tissue profusion and permeability. This research aims to summarize the clinical evidence on Sustained Acoustic Medicine and measurable outcomes in the literature. Methods A systematic literature review was conducted using PubMed, EBSCOhost, Academic Search Complete, Google Scholar and ClinicalTrials.gov to identify studies evaluating the effects of Sustained Acoustic Medicine on the musculoskeletal system of humans. Articles identified were selected based on inclusion criteria and scored on the Downs and Black checklist. Study design, clinical outcomes and primary findings were extracted from included studies for synthesis and meta-analysis statistics. Results A total of three hundred and seventy-two participants (372) were included in the thirteen clinical research studies reviewed including five (5) level I, four (4) level II and four (4) level IV studies. Sixty-seven (67) participants with neck and back myofascial pain and injury, one hundred and fifty-six (156) participants with moderate to severe knee pain and radiographically confirmed knee osteoarthritis (Kellgren-Lawrence grade II/III), and one hundred forty-nine (149) participants with generalized soft-tissue injury of the elbow, shoulder, back and ankle with limited function. Primary outcomes included daily change in pain intensity, change in Western Ontario McMaster Osteoarthritis Questionnaire, change in Global Rate of Change, and functional outcome measures including dynamometry, grip strength, range-of-motion, and diathermic heating (temperature measurement). Conclusion Sustained Acoustic Medicine treatment provides tissue heating and tissue recovery, improved patient function and reduction of pain. When patients failed to respond to physical therapy, Sustained Acoustic Medicine proved to be a useful adjunct to facilitate healing and return to work. As a non-invasive and non-narcotic treatment option with an excellent safety profile, Sustained Acoustic Medicine may be considered a good therapeutic option for practitioners.